Preparation of Proanthocyanidins Microcapsules Using Maillard Reaction Products of Whey Protein Isolate-D-Xylose and Study on Their Properties - Lei JING; Lele CHEN; Dexiu ZHAO; Dongmei YANG; Zijun CHU; Xiaojun YANG (Shipin gongye ke-ji)
In this study, a composite wall material was prepared by blending whey protein isolate-D-xylose mixture and their Maillard reaction product with sodium alginate, which were then used for encapsulating proanthocyanidin to fabricate proanthocyanidin microcapsules. By characterizing the morphology, investigating stability, and assessing the in vitro antioxidant activity of different proanthocyanidin microcapsules, the advantages of microencapsulation of proanthocyanidin and the superiority of using Maillard reaction product as a wall material were elucidated. The results indicated that the microcapsules formed using the Maillard reaction product achieved an encapsulation efficiency of 98.60%±0.09%, with a proanthocyanidin content of 49.97±0.87 mg/g and a particle size of 1219.61±388.24 μm, exhibiting good granular morphology. Compared to microcapsules without the Maillard reaction, those formed with it demonstrated enhanced stability under conditions of 90 ℃, pH≤4, pH=10, and in gastric digestion fluid. Furthermore, when the proanthocyanidin concentration reached 30 μg/mL, the microcapsules formed with the Maillard reaction product exhibited stronger in vitro antioxidant activity. This study lays the groundwork for further development and utilization of proanthocyanidin microcapsules, offering new insights into the development and advancement of proanthocyanidin microcapsule food products.